Cystatin C regulates the cytotoxicity of infection‐induced endothelial‐derived β‐amyloid. Issue 11 (25th October 2020) - Balczon, Ron; Morrow, Kyle A.; Leavesley, Silas; Francis, Christopher M.; Stevens, Trevor C.; Agwaramgbo, Ezinne; Williams, Christopher; Stevens, Reece P.; Langham, Geri; Voth, Sarah; Cioffi, Eugene A.; Weintraub, Susan E.; et al.
Abstract : Infection of rat pulmonary microvascular endothelial cells with the bacterium Pseudomonas aeruginosa induces the production and release of cytotoxic oligomeric tau and beta amyloid (Aβ). Here, we characterized these cytotoxic amyloids. Cytotoxic behavior and oligomeric tau were partially resistant to digestion with proteinase K, but cytotoxicity was abolished by various denaturants including phenol, diethylpyrocarbonate (DEPC), and 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐isopropanol (HFIP). Ultracentrifugation for 8 h at 150 000 g was required to remove cytotoxic activity from the supernatant. Ultracentrifugation, DEPC treatment, and immunodepletion using antibodies against Aβ also demonstrated that cytoprotective protein(s) are released from endothelial cells during P. aeruginosa infection. Mass spectrometry of endothelial cell culture media following P. aeruginosa infection allowed identification of multiple potential secreted modulators of Aβ, including cystatin C, gelsolin, and ApoJ/clusterin. Immunodepletion, co‐immunoprecipitation, and ultracentrifugation determined that the cytoprotective factor released during infection of endothelial cells by P. aeruginosa is cystatin C, which appears to be in a complex with Aβ. Cytoprotective cystatin C may provide a novel therapeutic avenue for protection against the long‐term consequences of infection with P. aeruginosa . Abstract : Infection of pulmonary endothelial cells by Pseudomonas aeruginosa induces the production and release of cytotoxic oligomeric tau and Aβ from the endothelial cells. Cystatin C, which is also secreted by the endothelial cells, can suppress the cytotoxic activity of Aβ. Whether cystatin C directly impacts oligomeric tau remains to be determined. Image produced with BioRender.